Population densities and conservation assessment of three threatened agamid species in Horton Plains National Park, Sri Lanka - Jayasekara, D; Keerthirathna, L; Mahaulpatha, D. (Journal of Wildlife and Biodiversity, 2020)
Horton Plains National Park is home for three endemic and threatened agamid species in Sri Lanka; Ceratophora stoddartii, Cophotis ceylanica and Calotes nigrilabris. This study was conducted to estimate the population densities of these lizard species within HPNP in 2016 and 2017. Line transect surveys were carried out following the "Distance" method to obtain population counts. A total of 288 transects were surveyed in two different time periods of each year; Dry months and Wet months. The program "Distance 7.1" was used for density calculations. The highest population density was recorded for Ce. stoddartii in the wet months of 2016 and 2017 (32.91 ind/ha, n=77; 26.70 ind/ha, n=66). However, Ce. stoddartii density was relatively lower in the dry months of both years (2016: 19.79 ind/ha, n=58; 2017: 17.18 ind/ha, n=55). The lowest population density was recorded for Ca. nigrilabris in the wet season of 2017 (7.80 ind/ha, n=38). The population density of Co. ceylanica which did not show much fluctuation throughout all four sampling periods, was relatively lower when compared with other species. These results indicate that more conservation focus is required to protect these agamids that have low and declining populations when compared to past literature available. They are also facing the threat of illegal smuggling.
Keywords: Agamidae, cloud forests, conservation, distance method, lizard smuggling, threatened lizards